2018
DOI: 10.1039/c8tc00182k
|View full text |Cite
|
Sign up to set email alerts
|

Double carbon dot assembled mesoporous aluminas: solid-state dual-emission photoluminescence and multifunctional applications

Abstract: Double carbon dot-based fluorescent materials synthesised in one step possess dual characteristic peaks and multifunctional applications in WLED and transparent sunlight conversion film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…As fluorescent carbon nanomaterials with a size less than 10 nm, carbon quantum dots (CQDs) have good water solubility, excellent chemical inertness, unique resistance to light bleaching, low toxicity, and good biocompatibility, etc. Due to their unique optical properties of tunable photoluminescence and good fluorescent stability, CQDs have been widely used in white light emitting diodes (white LEDs) [1][2][3][4]. In particular, published experimental results have shown that CQDs have great application potential in white LEDs as phosphors [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As fluorescent carbon nanomaterials with a size less than 10 nm, carbon quantum dots (CQDs) have good water solubility, excellent chemical inertness, unique resistance to light bleaching, low toxicity, and good biocompatibility, etc. Due to their unique optical properties of tunable photoluminescence and good fluorescent stability, CQDs have been widely used in white light emitting diodes (white LEDs) [1][2][3][4]. In particular, published experimental results have shown that CQDs have great application potential in white LEDs as phosphors [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Traditional methods are available to obtain long‐wavelength‐emission CDs through complex material design, multistep purification, and bandgap engineering. [ 30 ] Although the researchers synthesized long‐wavelength emission CDs, they had to face the dilemma: the CDs have low photoluminescence quantum yield (PLQY) and poor stability. [ 31 ] For example, Wang et al reported the design and implementation of solid white‐light‐emitting phosphors (WCDs@PS), which combine blue and orange emissive CDs (BCDs and OCDs) assisted by polystyrene (PS).…”
Section: Introductionmentioning
confidence: 99%
“…12 Electrostatic force or electrostatic interaction between the CD molecules disturbs their electrostatic stability during agglomeration and thus causes quenching in liquid CDs. 5,13 To resolve the quenching effect of CDs, liquid CDs were dispersed in a single matrix including silica, 14 mesoporous alumina, 15 and several polymers such as polyvinylpyrrolidone (PVP), polyacrylic acid (PAA), polyacrylamide (PAM), 16 polymethyl methacrylate (PMMA), poly(N-isopropylacrylamide) (PNIPAM), 17 and polyvinyl alcohol (PVA). 8,9,[17][18][19][20][21] All of these CDs/ polymer composite lms absorb only in the UV region.…”
Section: Introductionmentioning
confidence: 99%